A free-standing nitrogen-doped porous carbon foam electrode derived from melaleuca bark for lithium-sulfur batteries. (10th January 2019) - Zhu, Qiancheng; Deng, Huihui; Su, Qingmei; Du, Gaohui; Yu, Yuan; Ma, Shufang; Xu, Bingshe
Abstract: Lithium-sulfur (Li-S) battery is an appealing technology due to its conspicuous advantages in the area of energy storage. However, many challenges remain, such as the design of cathode with high sulfur loading, suppression of shuttle effects, enhanced performance and large scale preparation. Here, we report a novel 3D free-standing nitrogen-doped porous carbon foam (PCF) obtained by carbonization of the natural melaleuca bark, and apply it as a binder-free current collector to host sulfur for Li-S cells. This study shows that the obtained N-doped PCF possesses sheet-like porous carbon structures, high specific surface area, and large pore volume. Taking advantage of these properties, the resulting PCF/S electrodes exhibit an initial discharge capacity of 1330 mAh g −1, good reversible capacity of 880 mAh g −1 after 100 cycles at 0.2 C and deliver an excellent cycling stability (over 250 cycles at 0.5 C with 0.14% capacity fading per cycle). In addition, the PCF/S electrodes with large areal mass loading of 6 mg cm −2 show a high areal capacity of 4.14 mAh cm −2, revealing a great potential for high energy Li-S batteries. Graphical abstract: Image Highlights: 3D structured N-doped porous carbon foam (PCF) was derived from melaleuca bark. Li-S batteries are assembled with PCF as free-standing cathode supporters. PCF/S electrode exhibits high area capacity of 4.14 mAh cm −2 at 0.2 C. High porosity and conductivity of PCF contribute to excellent performance.